Chas. Ben. Darwin, Ordinances of the City of Burlington 108 (1856) - (:unkn) unknown (My University, 1854)
§ 19: Prohibited discharging any gun, pistol, or other firearm within any highway or thoroughfare. Violators guilty of a misdemeanor.
Keywords: DISCHARGE